The Role of Good Corporate Governance in Moderating the Effect of Financial Performance on Firm Value: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange - Nita Priska Ambarita (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
-